The Effect of Light, Fertiliser and Planting Density on the Growth and Flowering of Asystasia Gangetlca Subsp. Micrantha - Quah, Yin Thye (1997)
Asystasia gangetica subsp. micrantha, commonly known as Asystasia, is a prolific weed that has recently become problematic to the plantation industry in Malaysia. The weed's success in invading plantations over a wide geographical range is attributed to its fast establishment, rapid growth rate and early flowering. The pot trial study of Asystasia showed the weed's life-cycle consists of four growth phases, each of about 45-days' duration: namely phase 1 juvenile, phase 2 initial flowering, phase 3 intense flowering and phase 4 - senescent. Phase 1 was characterised by rapid vegetative growth with the first flower blooming by Day 42. The total dry wei ght for high-density (17 plants/pot) plants under full sunlight and high soil nutrients was 34 g/pot . The dry matter partitioning of leaves: stems: roots was 40:28:32 and the leaf index was 5.37. The weed's fast growth from seed germination is one of its outstanding characteristics and has made it highly successful in colonising exposed sites brought about by land cultivation or chemical spraying. The second growth phase from Day 45 to 90 consisted of both vegetative and flowering. The total biomass has increased to 95 g/pot and dry matter partitioning of leaves: stems: roots has changed to 31:37:32. Emphasis of dry matter allocation has shifted from leaves to stems as the plant grew. This stage of growth could also be considered the "building phase" as the weed accumulated biomass and leaves for the next stage of high reproduction. Leaf index has more than doubled to 12.8. Inter-plant competition has affected flowering: low-density (1 plant/pot) plants have higher capsule potential of 302 capsules/pot compared to only 34 capsules/pot for high-density under open conditions with high fertiliser rates. Phase 3 growth of Asystasia was primarily the flowering and reproduction stage and these might be considered the "climax" growth. The total dry matter of 232 g/pot has more than doubled the previous phase but the capsule potential has increased many times. Flowering was intense. Under open conditions, capsule potential ranged from 325 to 1078 capsules/pot while under shade conditions, the potential was 285 to 820 capsules/pot. Dispersed seeds would become part of the soil seed bank and ready to germinate at the next growth opportunity and perpetuate future generations of Asystasia. Dry matter partitioning of leaves: stems:roots was 22:3 6:42. Leaf index has increased to 19.8. The last phase is senescence stage. Most of the ripe capsules have dispersed their seeds and most plants were chlorotic and suffering from considerable die-back.